(a+2)(a^2+4)(a^4+16)(a-2),用平方差公式计算,^后面是平方
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 15:27:30
(a+2)(a^2+4)(a^4+16)(a-2),用平方差公式计算,^后面是平方(a+2)(a^2+4)(a^4+16)(a-2),用平方差公式计算,^后面是平方(a+2)(a^2+4)(a^4+1
(a+2)(a^2+4)(a^4+16)(a-2),用平方差公式计算,^后面是平方
(a+2)(a^2+4)(a^4+16)(a-2),用平方差公式计算,^后面是平方
(a+2)(a^2+4)(a^4+16)(a-2),用平方差公式计算,^后面是平方
(a+2)(a^2+4)(a^4+16)(a-2)
=(a-2)(a+2)(a^2+4)(a^4+16)
=(a²-4)(a²+4)(a^4+16)
=(a^4-16)(a^4+16)
=a^8-256
(a+2)(a^2+4)(a^4+16)(a-2),
=(a-2)(a+2)(a^2+4)(a^4+16)
=(a^2-4)(a^2+4)(a^4+16)
=(a^4-16)(a^4+16)
=a^8-256
(
原式=(a+2)(a-2)(a^2+4)(a^4+16)
=(a^2-4)(a^2+4)(a^4+16)
=(a^4-16)(a^4+16)
=a^8-256
希望我的回答对你有帮助,谢谢
(1-16a×a×a×a)÷(4a×a+1)÷(2a+1)²
(1-16a×a×a×a)÷(4a×a+1)÷(2a+1)
化简(a/a-2-a/a+2)×4-a/a(a/a-2-a/a+2)×4-a/a
a^2-4a
计算;(a^3)^4+a^10×a^2-a×a^2-a*a^3*a^8
a-2a+3a-4a+5a-6a+...+99a-100a
化简; a-2a+3a-4a+5a-6a+``````-2006a+2007a.
(a+3a+5a+...+2009a)-(2a+4a+6a+...+2008a)=
(a+3a+5a+.+2009a)-(2a+4a+6a+.2008a)
计算(a+3a+5a+...+2009a)-(2a+4a+6a+...+2010a)
(a+3a+5a+...+2013a)-(2a+4a+6a+...+2012a)=
化简:a-2a+3a-4a+5a-6a+.+2010a+2011a.
计算(a+3a+5a+.+2003a)-(2a+4a+6a+...+2004a)
(a+3a+5a+.+2003a)-(2a+4a+6a+.+2004a)
(a+3a+5a...+2009a)-(2a+4a+6a+...+2010a)=?
a^2-16/a^2-2a-3 *a-3/a^2-5a+4 化简
a(a-1)(a-2)(a-3)(a-4)因式分解
【1】a+a=a×a a= [ ]【2】a×a=a÷a a=[ ]【3】a×a=a-a a=[ ] [4]a-a=a+a a=[ ]